TINJAUAN YURIDIS TERHADAP KEABSAHAN PEMBUATAN AKTA JUAL BELI TANAH OLEH PEJABAT PEMBUATAN AKTA TANAH YANG DIDUGA DIBUAT SECARA MELAWAN HUKUM (Studi Putusan Pengadilan Palembang No. 214 k/Pdt/2021) - Ashanti Nurshafira; Mohamad Fajri Mekka Putra (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
This research discusses the benchmarks in determining the establishment of the deed of sale and purchase of land which is considered to be determined whether it is against the law or not and the legal force of the certificate as the evidence, based on the decision of the District Court Number 214 k/Pdt/2021. The case was occured in Palembang, specifically in the Palembang District Court. The types and sources of the data that will be used in writing this research are divided into two, namely primary data and secondary data. In writing this research, there are two data collection techniques used which is library research and field research. The data obtained both primary and secondary data were analyzed using quantitative techniques and then presented descriptively. The credibility of the deed is questionable because the Land Deed Making Officer as a General Officer (hereinafter referred to as